Proposed Marketing Strategy for Senopati Penthouse Apartment (The Indonesian Journal of Business Administration, 2015)
Abstract.â€“ Senopati Penthouse (SPH) is an apartment product of PT Senopati Aryani Prima (SAP), the company faced an intense market competition. There are several strategy that can be performed such as (i) Perform internal & external analysis, etc. The result from the internal analysis shows that SPH has a weak level of branding recognition. While the external analysis shows that the competition in Jalan Senopati is very intense. The research methodology is quantitative and qualitative. In quantitative, questionnaires were handed to the customers, while the qualitative is more to interviews and discussions with the executive boards of the company. The primary data collection comes from the questionnaire and interview, whereas the secondary comes from articles, book, analysis, etc. The result is SPH needs to leverage its brand and also improve the quality of service to win the apartment competition.Keywords: Senopati Penthouse, Marketing Strategy, Marketing Mix, and STPÂ Â